2018
DOI: 10.1002/advs.201800703
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Anisotropic Hydrogels with Bioinspired Motion

Abstract: Motion in biological organisms often relies on the functional arrangement of anisotropic tissues that linearly expand and contract in response to external signals. However, a general approach that can implement such anisotropic behavior into synthetic soft materials and thereby produce complex motions seen in biological organisms remains a challenge. Here, a bioinspired approach is presented that uses temperature‐responsive linear hydrogel actuators, analogous to biological linear contractile elements, as buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…[ 227 ] The complex bioinspired shape motions could also be realized by combining two printed layers with different orientations (Figure 11D). [ 245 ] A wide range of sophisticated motions from simple bending to coiling and twisting were achieved (Figure 11E). Zhao and co‐workers developed DIW of an elastomer composite containing ferromagnetic microparticles to enable shape changing.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 227 ] The complex bioinspired shape motions could also be realized by combining two printed layers with different orientations (Figure 11D). [ 245 ] A wide range of sophisticated motions from simple bending to coiling and twisting were achieved (Figure 11E). Zhao and co‐workers developed DIW of an elastomer composite containing ferromagnetic microparticles to enable shape changing.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…Reproduced with permission. [ 245 ] Copyright 2019, John Wiley and Sons. E) Various 3D complex shapes could be achieved through controlling the width and angle between the long axis of a bilayer structure in (D) and the direction of the intrinsic curvature (scale bars = 5 mm).…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…h) DIW of thermally responsive poly( N ‐isopropylacrylamide) hydrogel containing non‐responsive poly(ethylene glycol) (PEG) components facilitating patterned uniaxial contraction. Reproduced with permission 482. Copyright 2015, RSC.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Spinks and co‐workers demonstrated that the rheological properties needed for controlled printing are accessible through the inclusion of high molecular weight polymer materials 481. Yum recently utilized a similar approach by DIW printing of isotropic PNIPAm hydrogels reinforced with poly(ethylene glycol) (PEG) polymer chains 482. By use of a fugitive carrier (a shear‐thinning material that can be selectively removed from the polymerized hydrogel matrix), a series of homogeneous, multilayer hydrogels are prepared from low molecular precursors.…”
Section: Hydrogelsmentioning
confidence: 99%
“…The results showed that the bioinspired zigzag designs and bioinspired sinusoidalarchitected designs have a relative higher impact energy, and FIGURE 7 | Heat-induced shape-changing structures fabricated by 3D printing technology. (A) Bioinspired shape-changing structures fabricated by temperature-responsive linear hydrogel (Arslan et al, 2018). Reproduced with the permission of WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Fiber-reinforced Structuresmentioning
confidence: 99%